Research on the coupling control mechanism of yielding-bolt-grouting in deep water-enriched roadway and its engineering application - Zhang, Jihua; Rui, Qiao; Wang, Lianguo; Yang, Yushun; Chen, Jiarui; Shen, Wei; Wang, Chengwu; Liu, Weili (Frontiers in Earth Science, 2025)
Groundwater seepage can easily cause large deformation and fracture instability of the surrounding rock in deep roadways, and the coupling support of “yield-bolt-grouting” can effectively control the occurrence of such accidents. This paper takes the specific engineering geological conditions of deep water-enriched roadway as the research background, revealing the coupling control mechanism of yield-bolt-grouting. The mechanical characteristics of the yielding tube were determined using lab analysis, and an investigation was conducted for the support control mechanism of high-strength yielding bolts. The control mechanism of grouting reinforcement is summarized, and a comprehensive coupling control technology system of “yield-bolt-grouting” is proposed based on the rheological large deformation characteristics of the surrounding rock of deep water-enriched roadway, with high-strength yielding grouting anchor rods and high-strength yielding grouting anchor cables as the core. The on-site monitoring results indicate that this technology effectively controls the deformation of the surrounding rock. The research results provide new ideas and technical approaches for controlling the surrounding rock of deep water-enriched roadways.